2005
DOI: 10.1021/ef050162m
|View full text |Cite
|
Sign up to set email alerts
|

Part 1. The Effect of Microwave Receptors on the Liquefaction of Turkish Coals by Microwave Energy in a Hydrogen Donor Solvent

Abstract: The effects of microwave receptors to coal (receptor/coal) ratio and the period of heating by microwave energy on the solubilization of Turkish coals (Tunçbilek, Mug̋la-Yatag̋an, Beypazarı lignites, and Zonguldak bituminous coal) in tetralin have been investigated. V2O5 and TiO2 were used as microwave receptors. The changes of liquid product yield indicated that it depended significantly on the type and amount of receptor and the type of coal. A significant increase in the lignite conversions to oil fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…It can be concluded that the increase in the MW receptor/coal ratio can significantly increase the product yield and accelerate the MW pyrolysis process. Similar results have been reported in the literature. ,,, The increased MW receptor/coal ratio resulted in higher heating rates and final pyrolysis temperature, which, in turn, increased the rate of primary products cracking, leading to a sharp increase in the yield of non-condensable gases, as shown in Figure .…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It can be concluded that the increase in the MW receptor/coal ratio can significantly increase the product yield and accelerate the MW pyrolysis process. Similar results have been reported in the literature. ,,, The increased MW receptor/coal ratio resulted in higher heating rates and final pyrolysis temperature, which, in turn, increased the rate of primary products cracking, leading to a sharp increase in the yield of non-condensable gases, as shown in Figure .…”
Section: Results and Discussionsupporting
confidence: 89%
“…Similar results have been reported in the literature. 32,38,47,48 The increased MW receptor/coal ratio resulted in higher heating rates and final pyrolysis temperature, which, in turn, increased the rate of primary products cracking, leading to a sharp increase in the yield of non-condensable gases, as shown in Figure 3.…”
Section: Effect Of the Residence Time And Mw Receptor/coalmentioning
confidence: 99%
“…This high temperature is obtained because of the absorption of microwaves by the carbon which was applied as a bed. In addition to the use of carbon and graphite, oxides of metals are also reported as microwave absorbing materials . These materials may absorb microwaves and generate heat because of the vibrational relaxations.…”
Section: Introductionmentioning
confidence: 99%
“…21 By this way, the copper vanadate precursor could be employed to obtain copper nanoparticles and vanadium pentoxide (V 2 O 5 ). Especially, previous reports suggested that V 2 O 5 could strongly enhance the microwave adsorption capability, 22 which could promote the reduction rate of copper. Moreover, V 2 O 5 was important to improve surface adsorption due to its redox and Lewis acid-base properties.…”
Section: Introductionmentioning
confidence: 99%